2018
DOI: 10.1038/s41564-018-0199-2
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli translation strategies differ across carbon, nitrogen and phosphorus limitation conditions

Abstract: For cells to grow faster they must increase their protein production rate. Microorganisms have traditionally been thought to accomplish this increase by producing more ribosomes to enhance protein synthesis capacity, leading to the linear relationship between ribosome level and growth rate observed under most growth conditions previously examined. Past studies have suggested that this linear relationship represents an optimal resource allocation strategy for each growth rate, independent of any specific nutrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
137
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 58 publications
15
137
1
Order By: Relevance
“…The method for total RNA and protein measurements is described in (Li et al, 2018 Chemostat variables _ = +,_ , 3,_ , … 5,_ Nutrient environment inside the -th chemostat.…”
Section: Methods 708mentioning
confidence: 99%
“…The method for total RNA and protein measurements is described in (Li et al, 2018 Chemostat variables _ = +,_ , 3,_ , … 5,_ Nutrient environment inside the -th chemostat.…”
Section: Methods 708mentioning
confidence: 99%
“…3C). 24 , we observe that the total amount of protein is generally not affected by limiting carbon or nitrogen, nor by supplementing the cells with excess of either nutrient. However, perhaps most interestingly, we additionally find that when phosphorus is limited (0.25X), excess carbon supplementation not only rescues the growth rate of the culture (Fig.…”
Section: High-throughput Perturbation Analysis Of Metabolitesmentioning
confidence: 65%
“…It has traditionally been thought that cells regulate protein production by allocating their resources to optimize for both expression and growth 22,23 . However, it has recently been shown that in either carbon-, nitrogen-or phosphorus-limiting conditions, cells are able to fine-tune their ribosomal usage to maintain equal levels of protein 24 . Thus, we hypothesized that exploration of the entire metabolite landscape (Fig.…”
Section: High-throughput Perturbation Analysis Of Metabolitesmentioning
confidence: 99%
“…For example, some species exhibit a loss of ribosomes during extended periods of stationary phase (Deutscher, 2003; Piir et al, 2011) which would be expected to decrease overall protein synthesis. However, recent work suggests that ribosomes are actually in excess, and that only a fraction are active, especially under non-exponential growth (Dai et al, 2016; Li et al, 2018). This excess would be particularly useful for the exit from quiescence, since the ability to transition to maximal protein synthesis as quickly as possible would provide a clear selective advantage (Korem Kohanim et al, 2018; Remigi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%